The role of CA-125 level in diagnosis of ectopic pregnancy and threatened abortion - Ramezanpour, Mahsa; Aghazade naini, Afsaneh; Rahmanian, Ehsan; Halali, Majidreza (Student Research in Translational Medicine, 2019)
Objectives: Determination of the best diagnostic methods for ectopic pregnancy (EP) and threatened abortion is an issue of importance specially to improve the final prognosis. The purpose was to determine the CA-125 level in cases of EP and threatened abortion in comparison with control subjects. Methods: In this cross-sectional study,90 consecutive women attending to Shohada-e-Tajrish and Mahdieh Hospitals in Tehran including those with EP and threatened abortion and control subjects were enrolled and CA-125 level was determined and compared across the three groups. Results: The results in this study demonstrated that CA-125 level was significantly different across the groups (P=0.005) and in paired comparisons it was higher in threatened abortion cases versus control subjects (P=0.003) but it was not significantly differed between the other groups (P > 0.05). Conclusion: Totally, according to the obtained results it may be concluded that serum CA-125 level is higher in threatened abortion cases but not significantly in EP cases. Hence use of this method is recommended in clinical setting for threatened abortion.